Experiences of Stigma by Gay and Bisexual Men in Rural Oklahoma - Randolph D. Hubach; Joseph M. Currin; Zachary Giano; Hunter J. Meyers; Kyle R. DeBoy; Denna L. Wheeler; Julie M. Croff (Mary Ann Liebert, 2019)
Purpose: The unique experiences of men who have sex with men (MSM) residing in culturally conservative rural areas are not well represented in the scientific literature. The human immunodeficiency virus (HIV) epidemic in the United States has shifted toward rural areas where populations are dispersed and health care resources are limited. Methods: We recruited 40 sexual minority men, ages 22?66, residing in rural Oklahoma for in-depth, qualitative sexual health interviews that sought to understand how cultural and social environments impacted health behaviors. Findings: Participants described a stigmatizing social environment and less access to quality, sexual minority medical care within rural communities and perceived these as substantial barriers to enhancing health. Structural issues, including lack of sexual minority-affirming policies, institutional practices, and hostile cultural norms, were noted. Conclusions: Results indicate the need to develop greater awareness of stigma as an etiologic factor that contributes to the health of rural sexual minority populations, specifically when it relates to provision of culturally appropriate care.